High-strength gray cast iron
By optimizing the composition design of high-strength gray cast iron, ensuring its metallographic structure and graphite morphological characteristics, the problem of insufficient strength of existing gray cast iron is solved, and the effect of high tensile strength is achieved. It is suitable for high-horsepower diesel engine components.
Patent Information
- Application Number
- CN202411619886.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-13
AI Technical Summary
Existing gray cast iron cannot meet the ever-increasing explosive and impact force requirements in high-horsepower diesel engine components, resulting in insufficient strength and performance.
By optimizing the composition design, we ensure that the pearlite proportion in the metallographic structure of high-strength gray cast iron reaches more than 98%, the proportion of graphite morphology of type A reaches more than 93%, and the size level of type A graphite is controlled to be 5-7.
The tensile strength of high-strength gray cast iron has been significantly improved to reach more than 505MPa, meeting the demand for material strength performance of high-power diesel engine components.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to high-strength grey cast iron, which has excellent strength characteristics and can be widely used in cylinder blocks, cylinder heads, crankshafts, camshafts, shaft sleeves and other parts of high-horsepower diesel engines. Background Art
[0002] The cross section of gray cast iron is gray, and the graphite in the matrix structure exists in the form of flakes. The flake graphite gives gray cast iron good shock absorption and thermal conductivity. Therefore, gray cast iron becomes the preferred material for diesel engine cylinder blocks, cylinder heads, crankshafts and other components.
[0003] As the market demand for diesel engine horsepower becomes higher and higher, the explosive force and impact force faced by its cylinder block, crankshaft and other components during operation are also increasing. Therefore, the requirements for the strength performance of gray cast iron materials of these components are also continuously improved.
[0004] Based on the above problems, developing high-strength gray cast iron to adapt to the current development trend of diesel engines has become one of the main research directions of the industry. Summary of the invention
[0005] The present invention provides a high-strength gray cast iron, in which the proportion of pearlite in the metallographic structure of the high-strength gray cast iron is more than 98%, and the proportion of graphite in the A-type morphology reaches more than 93%. The gray cast iron of the present invention exhibits excellent strength performance, and the as-cast tensile strength reaches more than 505MPa.
[0006] The technical objectives of the present invention are achieved by the following means.
[0007] The object of the present invention is to provide a high-strength gray cast iron, the components of which are calculated by mass percentage: C: 2.5-3.5%, Si: 1.0-1.8%, Mn: 0.6-1.5%, Cr≤0.4%, Mo: 0.3-0.7%, Cu: 0.6-1.3%, V: 0.03-0.09%, B: 0.005-0.01%, P≤0.18%, S≤0.15%, the remainder is Fe and unavoidable impurities, and the mass percentage of V and B satisfies: V / B=4.9-13.1.
[0008] Next, the composition design principle of the present invention is introduced.
[0009] C: Carbon is an element that improves the fluidity of molten iron, promotes graphitization, and is also the most basic strengthening element. However, too high a carbon content will cause serious coarsening of graphite in the matrix structure, which will deteriorate the strength of gray cast iron. Too low a carbon content will result in insufficient strengthening effect, reduced fluidity of molten iron, increased casting defects, and reduced mechanical properties of castings. Considering the casting performance and strength requirements, the present invention sets the carbon content to 2.5-3.5%.
[0010] Si: Silicon has a similar effect to carbon. It is also an element that improves the fluidity of molten iron and has the function of promoting graphitization and strengthening the matrix. Too much silicon will lead to too high carbon equivalent, thereby aggravating the coarsening of graphite in the matrix and deteriorating the strength of gray cast iron. Too low silicon content will lead to insufficient strengthening effect and fluidity of molten iron, increase casting defects, and the mechanical properties of castings cannot be guaranteed. Comprehensive casting performance to obtain strength requirements, the present invention sets the silicon content to 1.0-1.8%.
[0011] Mn: Manganese helps to obtain pearlite structure, can increase the content of pearlite, refine the structure, and improve the strength of gray cast iron. For the present invention, it is expected to obtain the metallographic structure of pearl 98, so the content of manganese is crucial to the present invention. However, too high a manganese content will lead to an increase in the number of carbides, resulting in a decrease in the continuity of the matrix and a deterioration in mechanical strength. In order to ensure a suitable metallographic structure and strength performance, the manganese content of the present invention is set to 0.6-1.5%.
[0012] Cr: Chromium is a pearlite stabilizing element that can increase the solubility of carbon in austenite, thereby promoting the formation of pearlite and refining the pearlite structure, thereby increasing the strength of gray cast iron. However, chromium easily combines with carbon to form carbides, resulting in an increased tendency of gray cast iron to white cast iron. The present invention sets the Cr content to less than 0.4%.
[0013] Mo: Molybdenum can effectively refine the pearlite structure, reduce the interlamellar spacing of pearlite, and prevent graphite from coarsening, thereby significantly improving the strength properties of gray cast iron. However, the effect of molybdenum on inhibiting ferrite is not obvious, so the amount of molybdenum should be controlled. The content of molybdenum in the present invention is set to 0.3-0.7%.
[0014] Cu: Copper is an element that promotes graphitization, can reduce the tendency of white cast iron and optimize the shape and size of graphite. Copper is a pearlite stabilizing element, which can promote the acquisition of pearlite structure and refine pearlite. The addition of copper can greatly improve the strength of gray cast iron. However, if the copper content is too high, the graphite morphology tends to transform to type B, type D, and type E, which is not conducive to maintaining the strength of gray cast iron. In summary, the copper content of the invention is controlled at 0.6-1.3%.
[0015] V, B and V / B: Vanadium is conducive to grain refinement, thereby improving the strength of gray cast iron, and trace amounts of boron can improve the hardenability of gray cast iron, thereby effectively inhibiting the growth of graphite during the cooling process of gray cast iron, and controlling the size and uniform distribution of graphite. The inventors of the present invention have found that on the basis of adding V and B at the same time, the content relationship between the two is synergistically controlled, and the content and size of type A graphite in gray cast iron are effectively regulated, thereby maximizing the strength of gray cast iron. By controlling V / B within a reasonable range, the content of type A graphite in the gray cast iron structure can reach more than 93%, and the size grade can reach 5-7 levels. A graphite morphology that is nearly all type A and small in size can be obtained, thereby ensuring that gray cast iron has the best strength characteristics. In order to obtain the above-mentioned effect, the present invention controls the addition amount of V to 0.04-0.09% and the addition amount of B to 0.005-0.001%. At the same time, based on a large number of experimental summaries, the most suitable range of V / B is determined to be 4.9-13.1.
[0016] P, S: Phosphorus and sulfur are impurity elements, which are inevitably introduced by the raw materials. The presence of the two has a negative impact on the strength properties of gray cast iron, and phosphorus can also cause cold brittleness. However, they also have positive effects. For example, phosphorus is a pearlite-forming element, which is conducive to the acquisition of pearlite structure. Sulfur can be combined with manganese to improve the machinability of gray cast iron and promote graphitization. Considering the cost and performance comprehensively, the phosphorus content of the present invention is limited to less than 0.18%, and the sulfur content is limited to less than 0.15%.
[0017] The high-strength gray cast iron of the present invention having the above-mentioned composition, according to the detection and analysis of GB / T7216-2023, has a graphite morphology including type A graphite, the proportion of type A graphite is not less than 93%, and the size grade of the type A graphite is 5-7, showing a fine feature, reducing the splitting effect on the organization, thereby obtaining higher strength performance. Preferably, the high-strength gray cast iron of the present invention has a full A-type graphite organization morphology.
[0018] According to the detection and analysis of GB / T7216-2023, the proportion of pearlite in the metallographic structure of the high-strength gray cast iron of the present invention is not less than 98%, that is, it reaches the metallographic requirement level of pearlite 98.
[0019] The high-strength gray cast iron having the above-mentioned graphite morphology and metallographic structure has a tensile strength of more than 505 MPa.
[0020] As a further limitation, the mass percentage of Si and C in the high-strength gray cast iron of the present invention satisfies: C+Si / 3=3.3-3.8%. If the carbon equivalent is too high, although the molten iron has good fluidity and small casting defects, the graphite is seriously coarsened, resulting in reduced strength performance of the gray cast iron. If the carbon equivalent is too low, the molten iron has poor fluidity and many casting defects, which also leads to reduced strength performance of the gray cast iron. Taking the above into consideration, the present invention sets the carbon equivalent C+Si / 3 in the range of 3.3-3.8%.
[0021] As a further limitation, the mass percentages of Si and C in the high-strength grey cast iron of the present invention satisfy: Si / C=0.48-0.62. Within the aforementioned range of carbon equivalent, a suitable Si / C is beneficial to improving the tensile strength of the grey cast iron.
[0022] As a non-limiting description, the high-strength gray cast iron of the present invention can be subjected to stress relief annealing after casting. Through the stress relief annealing, the stress generated by solidification and cooling during the casting process is eliminated, which can effectively increase the service life of the casting.
[0023] As a further description, the high-strength gray cast iron of the present invention is applied to diesel engine cylinder blocks, cylinder heads, camshafts, crankshafts, sleeves and other parts. These parts are usually made of gray cast iron materials with excellent wear resistance and thermal conductivity. In addition to the excellent wear resistance and thermal conductivity of conventional gray cast iron, the high-strength gray cast iron of the present invention also has excellent strength performance, so that the high-strength gray cast iron of the present invention can be well adapted to the performance requirements of high-horsepower diesel engines for materials.
[0024] In addition, the present invention also provides the application of the high-strength gray cast iron in diesel engine cylinder blocks, cylinder heads, camshafts, crankshafts, sleeves and other components. The high-strength gray cast iron of the present invention has excellent strength and outstanding impact resistance, and can be widely used in related parts of high-horsepower diesel engines.
[0025] The present invention has the following beneficial effects: the present invention adopts Cu and Mo to alloy the gray cast iron, and effectively improves the tensile strength of the gray cast iron. In particular, the present invention adds V and B elements, and synergistically controls the content relationship of V and B, effectively regulates the content and size of type A graphite in the gray cast iron, thereby maximizing the strength of the gray cast iron. The present invention controls the composition so that the proportion of type A graphite in the gray cast iron is not less than 93%, and the size grade of the type A graphite is 5-7, and the tensile strength of the gray cast iron finally obtained reaches above 505MPa. DETAILED DESCRIPTION
[0026] In order to enable ordinary technicians in the field to fully understand the technical solutions and beneficial effects of the present invention, further explanation is given below in conjunction with specific test examples.
[0027] According to the designed composition, the molten iron is smelted and cast into gray cast iron ingots. The smelting temperature is 1485°C, the pouring temperature is 1365°C, the size of the gray cast iron ingot is 500 mm long × 200 mm wide × 200 mm high. The specific composition is shown in Table 1. The contents of P and S are controlled at 0.1±0.01%. The metallographic structure of the obtained gray cast iron ingot is analyzed with reference to GB / T7216-2023, and the tensile strength is tested with reference to GB / T228.1-2021. The specific metallographic structure and tensile strength test results are shown in Table 2.
[0028] Table 1: Composition of various grey cast irons, %, the remainder is Fe.
[0029]
[0030] Table 2: Metallographic structure and strength of various gray cast irons.
[0031]
[0032] The above embodiments and comparative examples are further analyzed and explained below in conjunction with Tables 1-2.
[0033] The compositions of the gray cast irons of test numbers 1-10 all meet the requirements of the present invention. Through metallographic testing, it is found that the gray cast irons can satisfy a type A graphite ratio of more than 93%, a size grade of type A graphite of 5-7, and a pearlite quantity of more than 98%. Through mechanical property testing, it is found that the tensile strength of the gray cast irons is all above 505 MPa, with outstanding mechanical properties, showing good metallographic morphology and excellent mechanical property characteristics.
[0034] Test numbers 11-13 and 17 adjusted the V and B contents of test numbers 2, 3, 4 and 9 respectively. The adjusted V and B were still within the requirements of the present invention, but V / B no longer met the requirements of the present invention. The final test results showed that the amount of type A graphite in the gray cast iron could not meet the requirements of the invention, the tensile strength of the gray cast iron could not reach 505 MPa, and the size of type A graphite also showed varying degrees of coarsening. The size of type A graphite in test numbers 11, 12, 13 and 17 exceeded the scope required by the present invention.
[0035] Test No. 14 adjusted the V content of Test No. 5. The adjusted V content was not within the scope of the present invention, and V / B no longer met the requirements of the present invention. The final test results showed that the amount of type A graphite in the gray cast iron could not meet the requirements of the invention, the tensile strength of the gray cast iron could not reach 505 MPa, and the size of the type A graphite also became coarse.
[0036] Test No. 15-16 adjusted the B content of Test No. 7-8. The adjusted V / B met the requirements of the present invention, but the B content was not within the scope of the present invention. The final test results showed that the amount of type A graphite in the gray cast iron could not meet the requirements of the invention, the tensile strength of the gray cast iron did not reach 505 MPa, and the size of type A graphite also showed varying degrees of coarsening. The size of type A graphite in test No. 16 exceeded the scope required by the present invention.
[0037] By comparing Examples 1-10 and Comparative Examples 11-17, it is not difficult to find that controlling V, B, and V / B within appropriate ranges is crucial for obtaining A-type graphite with a specific amount and size and gray cast iron with excellent tensile strength.
[0038] In addition, the gray cast iron of test numbers 1, 5, and 10 of the present invention simultaneously meets the requirements of C+Si / 3 being in the range of 3.3-3.8% and Si / C being in the range of 0.48-0.62, and shows more excellent mechanical properties. The gray cast iron that meets the above conditions has a tensile strength of more than 535 MPa, indicating that controlling appropriate C+Si / 3 and Si / C is more conducive to improving the tensile strength performance of gray cast iron.
[0039] In summary, the present invention effectively regulates the content and size of type A graphite in gray cast iron by adding V and B elements and synergistically controlling the content relationship of V and B, thereby maximizing the strength of gray cast iron. The present invention controls the composition so that the proportion of type A graphite in gray cast iron is not less than 93%, and the size grade of type A graphite is 5-7, and the tensile strength of the gray cast iron finally obtained reaches more than 505MPa. It has excellent strength characteristics and metallographic structure, and is particularly suitable for application in diesel engine cylinder blocks, cylinder heads, camshafts, crankshafts, sleeves and other components.
[0040] The above embodiments are only used to help understand the method and core idea of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
[0041] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but will conform to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A high-strength grey cast iron, characterized in that: The composition of the high-strength gray cast iron is calculated by mass percentage: C: 2.5-3.5%, Si: 1.0-1.8%, Mn: 0.6-1.5%, Cr≤0.4%, Mo: 0.3-0.7%, Cu: 0.6-1.3%, V: 0.03-0.09%, B: 0.005-0.01%, P≤0.18%, S≤0.15%, the remainder is Fe and unavoidable impurities, and the mass percentage of V and B satisfies: V / B=4.9-13.
1.
2. The high-strength grey cast iron according to claim 1, characterized in that: The graphite form of the high-strength grey cast iron includes type A graphite, and the proportion of type A graphite is not less than 93%.
3. The high-strength gray cast iron according to claim 1, characterized in that: The size grade of the A-type graphite is 5-7.
4. The high-strength gray cast iron according to claim 1, characterized in that: The proportion of pearlite in the metallographic structure of the high-strength grey cast iron is not less than 98%.
5. The high-strength gray cast iron according to claim 1, characterized in that: The tensile strength of the high-strength grey cast iron is above 505 MPa.
6. The high-strength grey cast iron according to claim 1, characterized in that: The mass percentages of Si and C in the high-strength grey cast iron satisfy: Si / C=0.48-0.
62.
7. The high-strength grey cast iron according to claim 1, characterized in that: The mass percentages of Si and C in the high-strength grey cast iron satisfy: C+Si / 3=3.3-3.8%.
8. The high-strength grey cast iron according to claim 1, characterized in that: The high-strength grey cast iron may be subjected to stress relief annealing treatment after casting.
9. The high-strength grey cast iron according to claim 1, characterized in that: The high-strength grey cast iron is used for diesel engine cylinder blocks, cylinder heads, camshafts, crankshafts, shaft sleeves and other components.
10. Application of the high-strength grey cast iron according to any one of claims 1 to 9 in diesel engine cylinder blocks, cylinder heads, camshafts, crankshafts, sleeves and other components.
Citation Information
Patent Citations
Micro alloyed gray cast iron with ultrahigh strength and high carbon equivalent
CN102747267A
Gray cast iron and preparation method thereof
CN105200305A
Grey cast iron for brake components
GB1472292A
Gray cast iron
WO1994010354A1